Prenatal exposure to polychlorinated biphenyls is associated with markers of inflammation and oxidative stress in cord blood samples - Mohammed Merza; Enwa Felix Oghenemaro; Mohammed Asiri; Lalji Baldaniya; Ahmed Hjazi; Parjinder Kaur; Muhayyo Kholjigitova; Gulshan Rathore; M. Ravi Kumar; Moslem Lari Najafi (Environmental Sciences Europe)
Abstract The impacts of environmental pollutants on prenatal health are a growing concern, yet we still have limited understanding of how specific pollutants like polychlorinated biphenyls (PCBs) impact inflammation and oxidative stress in umbilical cord blood. This study explores how exposure to PCBs in umbilical cord blood relates to biomarkers of inflammation and oxidative stress in newborns. Between June 2019 and August 2021, we conducted a study with 450 pregnant women. We measured umbilical cord blood PCB levels using advanced Gas Chromatography-Mass Spectrometry (GC–MS). We also assessed key biomarkers Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-6 (IL-6), Interleukin-8 (IL-8), Transforming Growth Factor Beta (TGF-β), and Pro-oxidant Antioxidant Balance (PAB) using enzyme-linked immunosorbent assays (ELISA). To analyze the data, we employed multivariable regression models and quantile g-computation. Higher levels of specific PCBs were associated with increased levels of inflammatory markers like TNF-α and IL-6, as well as PAB. In particular, PCBs such as PCB-28, PCB-138, PCB-153, and PCB-180 were linked to elevated TNF-α and IL-6. The g-comp analysis also showed that as PCB levels increased, so did the levels of all five biomarkers, indicating a cumulative impact on inflammation and oxidative stress. This study is the first to link PCB exposure in umbilical cord blood with increased markers of inflammation and oxidative stress, shedding new light on the potential health risks for newborns. These findings highlight the importance of further research into how prenatal exposure to PCBs might affect long-term health outcomes.